Changing needs of medical education in Pakistan (Journal of Fatima Jinnah Medical University, 2020)
Medical education, encompasses a large variety of learning experiences. Broadly it includes premedical years, undergraduate education, house job clinical rotation, residency, subspecialty training, and continuous professional development. These phases of learning and training entails a medical student to become self-directed lifelong learner. The educationists acknowledge that traditional teacher centered medical education does not allow students to become self-directed learners. The changing expectations of society and newly defined roles of doctors’ envisage them to become lifelong learners, through continuous professional development.